Integrating Artificial Intelligence in Education Challenges and Opportunities for 21st Century Learning - Bashir Raza; Irfan Jameel Salman (International Forum of Researchers and Lecturers, 2022)
The integration of Artificial Intelligence (AI) in education presents both challenges and opportunities for 21st-century learning. This study explores the transformative potential of AI in enhancing personalized learning, adaptive assessments, and intelligent tutoring systems. The research aims to identify the key barriers to AI adoption in educational settings, including ethical concerns, data privacy, and technological infrastructure. Utilizing a qualitative approach, data were collected through literature reviews and expert interviews. The findings indicate that while AI can significantly improve learning outcomes and administrative efficiency, its implementation requires strategic planning, teacher training, and regulatory frameworks. This study highlights the importance of balancing AI-driven innovation with ethical considerations to maximize its benefits in education.